Antibiotic Resistance Patterns and Multidrug-Resistant Bacteria in Pediatric Patients: A Retrospective Study - Ali, Ghamela (AlQalam Journal of Medical and Applied Sciences, 2025)
The increasing prevalence of antibiotic-resistant bacteria is a major public health concern worldwide. Pediatric patients are particularly vulnerable to infections caused by resistant bacteria, which can lead to increased morbidity, mortality, and healthcare costs. This study aimed to investigate the distribution of bacterial species, antibiotic resistance patterns, and multidrug-resistant (MDR) bacteria in pediatric patients admitted to the pediatric ward (PW), neonatal intensive care unit (NICU), and pediatric intensive care unit (PICU) of Tobruk Medical Center in 2024. A retrospective study was conducted on 164 pediatric patients (aged 0–18 years) who underwent blood culture tests at Tobruk Medical Center in 2024. Data were collected from the hospital’s microbiology laboratory. The majority of patients were admitted to the PICU (n=75, 45.7%), followed by the PW (n=72, 43.9%). Most patients (86.6%) were under 5 years of age, with a mean age of 23.7 months. Sex distribution was relatively balanced, with a slight male predominance (n=84, 51.2%; M:F ratio 1.05:1). A total of 60 bacterial isolates were identified. Coagulase-negative Staphylococcus (CONS) and Staphylococcus aureus were the most common isolates (53.3% and 10%, respectively), followed by Klebsiella, E. coli, and Acinetobacter (each at 6.7%). Antibiotic resistance patterns revealed high resistance rates to: Beta-lactam antibiotics (16.7–20%), including ampicillin, ampicillin-sulbactam, amoxicillin-clavulanate, cefotaxime, and ceftriaxone. Fluoroquinolones (10–30%), including ciprofloxacin and levofloxacin. Carbapenems (11.7–15%), including imipenem, meropenem, and ertapenem. Penicillin and oxacillin (51.7% each). Low resistance rates were observed to Vancomycin (5%), linezolid (5%), and moxifloxacin (1.7%). Multidrug resistance (MDR) rate was alarmingly high: 68.3% (41/60) of isolates were resistant to one or more antibiotics across three or more classes. This study highlights alarming antibiotic resistance rates in pediatric patients, particularly to beta-lactams, fluoroquinolones, and carbapenems, with a high prevalence of MDR bacteria. However, vancomycin, linezolid, and moxifloxacin remain effective options due to their low resistance rates. The findings underscore the urgent need for judicious antibiotic use, enhanced infection control measures, and Continuous surveillance of resistance patterns to guide antibiotic stewardship programs and improve patient outcomes.